2014
DOI: 10.4081/ni.2014.5388
|View full text |Cite
|
Sign up to set email alerts
|

Highly expressed genes within hippocampal sector CA1: implications for the physiology of memory

Abstract: As the CA1 sector has been implicated to play a key role in memory formation, a dedicated search for highly expressed genes within this region was made from an on-line atlas of gene expression within the mouse brain (GENSAT). From a data base of 1013 genes, 16 were identified that had selective localization of gene expression within the CA1 region, and included Angpt2, ARHGEF6, CCK, Cntnap1, DRD3, EMP1, Epha2, Itm2b, Lrrtm2, Mdk, PNMT, Ppm1e, Ppp2r2d, RASGRP1, Slitrk5, and Sstr4. Of the 16 identified, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…In both the dCA1 and vCA1 subfields, the percentage of CCK-GABA cells was greater than PV-GABA cells ( p < 0.05, Figures 2A,B ). The relative abundance of CCK-GABA cells within the ventral hippocampus of CCK- Frepe mice is consistent with past reports, which show a relatively high density of CCK-GABA cells in this region ( Jinno and Kosaka, 2003b , 2006 ; Meyer, 2014 ). Further, we observed that PV-GABA cells were more numerous in the dSub ( p < 0.05, Figures 2A,B ), as shown previously ( Pitkanen and Amaral, 1993 ; Boccara et al, 2014 ).…”
Section: Resultssupporting
confidence: 92%
“…In both the dCA1 and vCA1 subfields, the percentage of CCK-GABA cells was greater than PV-GABA cells ( p < 0.05, Figures 2A,B ). The relative abundance of CCK-GABA cells within the ventral hippocampus of CCK- Frepe mice is consistent with past reports, which show a relatively high density of CCK-GABA cells in this region ( Jinno and Kosaka, 2003b , 2006 ; Meyer, 2014 ). Further, we observed that PV-GABA cells were more numerous in the dSub ( p < 0.05, Figures 2A,B ), as shown previously ( Pitkanen and Amaral, 1993 ; Boccara et al, 2014 ).…”
Section: Resultssupporting
confidence: 92%
“…For 22 genes, expression and localization studies have been performed by in-situ hybridization or immunohistochemistry (numbered in column 1). 1 (Kim et al, 2014), 2 (Vasiljevic et al, 2012) 3 (Konig et al, 2003), 4 (Blazejczyk et al, 2009), 5 (Dixon et al, 1997), 6 (Bohm et al, 2008), 7 (Yang et al, 2009), 8 (Masuda et al, 2014), 9 (Saitoh et al, 1993, 10 (Xiong et al, 2004), 11 (Bhat et al, 1994), 12 (Zhang et al, 2014), 13 (Sugita et al, 2002), 14 (Kanemaru et al, 2010), 15 (Meyer, 2014), 16 (Kuwajima et al, 1992), 17 (Sah et al, 1993), 18 (Sturchler et al, 2006), 19 (Vives et al, 2003), 20 (Mulder et al, 2010), 21 (Skibinska-Kijek et al, 2009), 22 (Saitoh et al, 1994) Gene name ISH Nr The results for the 135 genes clearly expressed in the 326 brain are presented in Table 2 Abbreviations: CA1/2/3: hippocampal fields; so: stratum oriens; sp: stratum pyramidale; sr: stratum radiatum; slm: stratum lacosum moleculare; DG: dentate gyrus; sg: granule cell layer; po: polymorph layer; hf: hippocampal fissure. ISH images for 17 genes, listed in alphabetical order, and presenting a characteristic expression pattern in the hippocampus, were taken from the ABA database.…”
Section: Nsc 16073mentioning
confidence: 95%
“…Among the clusters A and B, which consist of genes downregulated at E13 in comparison to E19 and controls, are genes such as neurotensin (Nts), a neuropeptide with anticonvulsant properties (Ferraro et al, 2011;Robertson et al, 2011), Rasgrp1, a stress-induced mammalian target of rapamycin (mTOR) repressor acting via Ras-ERK signaling and known to regulate Cybb (Daley et al, 2013;Meyer, 2014), Dpy19l1, heavily implicated in cortical development or Opalin, which is a paranodal protein associated with myelination (Watanabe et al, 2011;Yoshikawa et al, 2008). Gab1, found to be differentially expressed in microarray analysis, but not successfully verified via qPCR, perhaps due to strong interaction with seizurogenic treatment is also notable for its function in angiogenesis and regulatory action on mTOR via modulation of Egr-ERK signaling (Meng et al, 2005;Zhao et al, 2011).…”
Section: Functional Implications Of Altered Gene Expressionmentioning
confidence: 99%